Business and Newsroom Management of Indonesian Esports News Media - Yuwono, Ardian Indro; Dahana, Abyzan Syahadin Bagja (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2026)
Background: The popularity of esports in Indonesia has driven the emergence of esports journalism as an integral part of sports journalism. Unlike traditional sports, esports grew out of gaming culture, which makes esports journalism a distinctive practice. In Indonesia, this phenomenon has driven various digital-native media outlets focused on esports coverage. However, studies on how local media manage their editorial and business operations in this field remain limited. Purpose: This research explored how IndoGamers–one of the pioneers of esports media in Indonesia–performs its newsroom and business management functions. Methods: It used a case study method with primary data collected through interviews with four members of the newsroom team, along with secondary data, analyzed using the POAC management model (Planning, Organizing, Actuating, and Controlling). Results: The results show that the editorial process no longer relies on conventional news values but is entirely driven by Google trends and SEO logic. Nevertheless, IndoGamers provides in-depth news coverage, especially concerning the benefits of esports. Therefore, it does not merely portray esports as a form of entertainment. The division of journalistic tasks based on specific game specializations–without involving external contributors–demonstrates the dominance of platform logic in newsroom management. Conclusion: These findings affirm that esports journalism requires a management model responsive to data, real-time trends, and digital visibility demands. It offers theoretical and practical contributions to digital media studies and newsroom management in the algorithm era. Implications: Thus, IndoGamers’ practice of aligning editorial decisions with Google search trends and SEO logic demonstrates that data-driven strategies function not only to increase traffic, but also as a mechanism to maintain the relevance and accessibility of educational esports coverage while simultaneously fostering more positive and socially valuable narratives for audiences.